Histology of Small Intestinal in Hypothyroid Model Rats - Sherly Usman; Aisyah Luthfia Firdasari; Zulkhah Noor (Universitas Muhammadiyah Yogyakarta, 2021)
More than 700,000 people were diagnosed with hypothyroidism, in Indonesia case is quite large. The study aims to see differences in the histological features of villi epithelium small intestine mucosa hypothyroid rats. The design was experimental post only group. This hypothyroidism is obtained by giving daily drinks that have been mixed with 0.025% Propylthiouracil (PTU).Ten of Subjects were divided into 2 groups: group 1 (control) and group 2 (hypothyroid), each group consisted of 5 mice. The PTU treatment was carried out for 8 weeks. Decapitation was carried out with chloroform and Intestinal organs were taken by opening the stomach. Intestinal organ then processed into histological preparations. The preparations are seen for changes in the histological picture through a microscope by scoring the damage to the intestinal mucosa. Data analysis used the Shapiro-Wilk and Independent T test. In control group showed bleeding was moderate. In hypotyroidism group showed heavy bleeding intestinal mucosa, while necrosis and erosion showed mild criteria. This research is be able to provide scientific support through data regarding histology of the mucosal lining of the small intestine in hypothyroid rat models. Conclusion: Histology of small intestinal in hypotyroid model rats showed damage mucosa with erosion, bleeding and necrosis.